0206 Sleep Opportunity and Duration are Related to Risk Injury in Elite Athletes. (27th May 2020) - Shaw, L; Cohen, R; Altman, Y; Eyal, S; Baharav, A
Abstract: Introduction: Sleep is essential to musculoskeletal recovery, acquisition of new skills and emotional regulation in athletes. Insufficient sleep is detrimental to performance. Recent publications indicate that sleep duration is related to risk for injury in young athletes. We aimed at analyzing the relation between sleep opportunity and duration and the likelihood of an injury among adult elite athletes. Methods: We studied 7, 237 nights recorded with the Sleeprate application by 71 adult elite athletes from diverse sports, during the period September 2018-October 2019. Night recordings included perceived and measured sleep parameters. In addition, athletes reported their previous day nap duration, injuries and illness status. Out of the total number of nights, 4, 205 included reported injury status with no injury and no illness for the previous night. Nightly total time in bed (TIB), TIB including reported naps (TIB24hr) and measured total sleep time (TST) were examined. Results: Average TIB was significantly shorter (508±77 minutes, mean±STD) in healthy days preceding injuries than in healthy days preceding days with no injury (525±70 minutes, p<.001). Similar results were found when comparing the TIB24hr (injury: 517±83 minutes, no injury: 543±76 minutes, p<.001) and TST (injury: 443±72 minutes, no injury: 457±69 minutes, p<.001). Conclusion: Average sleep opportunities of the elite athletes in this study were in accordance with their age and workouts load. The time athletes allow themselves as an opportunity for sleep is inversely correlated to the chances of developing an injury. These findings corroborate published research regarding sleep duration and risk of injury in athletes, yet our findings are based on real life data of elite athletes, and demonstrate the importance of sleep as part of the elite or professional athlete's routine, suggesting that even as little as around 20 minutes of added sleep may be efficient in preventing injury. Support: N/A